∫ − ∞ ∞ ( x 2 + 1 ) 2 0 1 8 1 d x If the value of the above integral can be expressed as ( b c ⋅ c ! ) b a ! ⋅ π , for some positive integers a , b and c where b is prime. Find the largest value of a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Before to evaluate let's reduce the integral in the form of I n = ∫ ( a 2 + x 2 ) n + 1 1 d x ∀ n ∈ N . Here we will integrate it by parts so let us make u substitution as u = ( a 2 + x 2 ) n 1 and d v = d u which follows as d u = − ( a 2 + x 2 ) n + 1 2 n x d x and v = x . Hence, I n ∴ I n + 1 = ( a 2 + x 2 ) n x + 2 n ∫ ( a 2 + x 2 ) n + 1 x 2 d x = ( a 2 + x 2 ) x + 2 n ∫ ( a 2 + x 2 ) n + 1 a 2 + x 2 − a 2 = ( a 2 + x 2 ) x + 2 n I n − 2 n a 2 I n + 1 = 2 n a 2 1 ⋅ ( a 2 + x 2 ) n x + 2 n a 2 2 n − 1 ⋅ I n Set n = 2 0 1 7 and a = 1 we obtain I 2 0 1 8 = 4 0 3 6 1 ⋅ ( 1 + x 2 ) 2 0 1 8 x + 4 0 3 4 4 0 3 3 ⋅ I 2 0 1 7 Now setting limits from − ∞ to ∞ We obtain the following ∫ − ∞ ∞ I 2 0 1 8 = 0 + 4 0 3 2 4 0 3 3 ∫ − ∞ ∞ I 2 0 1 7 = 0 + 4 0 3 4 ⋅ 4 0 3 2 4 0 3 3 ⋅ 4 0 3 1 ∫ − ∞ ∞ I 2 0 1 6 = 0 + 4 0 3 6 ⋅ 4 0 3 4 ⋯ 2 4 0 3 3 ⋅ 4 0 3 1 ⋯ 1 ∫ − ∞ ∞ I 1 = ( 4 0 3 4 ) ! ! ( 4 0 3 3 ) ! ! π Since ( 2 n ) ! ! ( 2 n − 1 ) ! ! = ( 2 n n ! ) 2 ( 2 n ) ! = ( 2 2 0 1 7 ⋅ 2 0 1 7 ! ) 2 4 0 3 4 ! ⋅ π Thus, a + b + c = 4 0 3 4 + 2 0 1 7 + 2 = 6 0 5 3 .
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Beta Function
I = ∫ − ∞ ∞ ( x 2 + 1 ) 2 0 1 8 1 d x = 2 ∫ 0 ∞ ( 1 + x 2 ) n + 1 1 d x = ∫ 0 ∞ ( 1 + u ) n + 1 u − 2 1 d x = B ( 2 1 , 2 2 n + 1 ) = Γ ( n + 1 ) Γ ( 2 1 ) Γ ( 2 2 n + 1 ) = n ! π ( 2 n ( 2 n − 1 ) ! ! π ) = ( 2 n n ! ) 2 ( 2 n ) ! π Since the integrand is even Let n = 2 0 1 7 Let u = x 2 ⟹ d u = 2 x d x Beta function B ( j , k ) = ∫ 0 ∞ ( 1 + u ) j + k u j − 1 B ( j , k ) = Γ ( j + k ) Γ ( j ) Γ ( k ) where Γ ( ⋅ ) is the gamma function. As ( 2 n − 1 ) ! ! = 2 n n ! ( 2 n ) !
Therefore, a + b + c = 2 n + 2 + n = 3 ( 2 0 1 7 ) + 2 = 6 0 5 3 .